Modeling and Simulation of Magnetic Levitation System - Badrul Hisham, Muhammad Haris Fadhullah (Universiti Teknologi Petronas, 2011)
Overcoming the grip of the Earth's gravity has been a high-demand in current technology. Through work of engineers and scientist, human has found many ways to levitate a variety of objects to be applied in the field of mechanical and transportation. Magnetic levitation (Maglev) is a way of using electromagnetic fields to levitate objects without any contact with other material. However, magnetic levitation system is unstable and non-linear. This paper presents the mathematical modeling of the magnetic levitation system. Since magnetic levitation system is a non-linear system, it is controlled using Proportional Integral Derivative (PID) controller and Fuzzy Logic controller. The PID, Fuzzy Logic and Fuzzy-PID control techniques will be simulated and compared to determine which one of them give the best control performance to the system.